The Representation of Intercultural Values in the EFL Textbook for Senior High School - Maharani, Mela Olivia; Ariyanto, Sugeng; Suharjito, Bambang (English Education Study Program, 2023)
Abstract: This study was intended to describe the representation of cultural values in the ELT English textbook for senior high school students. The data collection used in this research is a documentary method. The data analysis method was Critical Discourse Analysis and Semiotic Analysis, focusing on two layering meanings, denotative and connotative, used to analyze the discourse of visual and textual form. The findings showed that there were 27 Source Cultures, 23 Target cultures, and 18 International cultures in the form of texts and images.